Improving harvest efficiency of maize varieties via accumulated temperature in a certain planting area - Huang, Zhaofu; Hou, Liangyu; Xue, Jun; Wang, Keru; Xie, Ruizhi; Hou, Peng; Ming, Bo; Li, Shaokun (International Journal of Agricultural and Biological Engineering, 2021)
The ripening and drying of maize (Zea mays L.) grain are closely related to temperature. In accordance with maize grain drying characteristics, regional accumulated temperature (AT00°C) distribution is of great significance for a rational allocation of maize varieties, thus reducing grain moisture content (MC) to improve maize harvest efficiency. From 2016 to 2018, a multi-site trial was carried out in the spring maize production area of Northeastern China. In this study, under a guaranteed rate of 80% for AT0, this area was divided into 15 accumulated temperature zones (ATZs) with an interval of 100°C based on climatic data of 78 local weather stations. Then the AT0 demand of different maize varieties during different growth stages was calculated by combining experimental records with the established prediction model of MC, and then, the spatial partition for different types of maize varieties under different MCs was analyzed. The results showed that all the tested varieties could not reach physiological maturity (PM) at ATZs 13-15, hence, where maize planting is risky. With the increasing accumulated temperature demand of different types of maize varieties from planting to PM, to the MC of 25% and to the MC of 20%, the unplantable areas were gradually expanded from south to north while the region where the maize varieties could be harvested under different MCs was also moved southwardly. Additionally, at 1-2 ATZs, it is entirely possible to achieve mechanical kernel harvesting under the MC of 20%, even though the AT0 requirements of the varieties are relatively high. Conclusively, on the grounds of AT0 demand law of maize varieties and heat resource distribution in Northeastern China, the layout optimization for achieving different harvesting scenarios is conducive to providing a basis not only for selecting suitable varieties but also for promoting mechanical kernel harvesting in the spring maize production area of this region. Keywords: grain, moisture content, accumulated temperature zone, cultivars’ layout, Northeastern China DOI: 10.25165/j.ijabe.20211404.6337 Citation: Huang Z F, Hou L Y, Xue J, Wang K R, Xie R Z, Hou P, et al. Improving harvest efficiency of maize varieties via accumulated temperature in a certain planting area. Int J Agric & Biol Eng, 2021; 14(4): 175–181.